Ecologia de mamíferos de médio e grande porte em uma paisagem agrícola no estado de São Paulo - Consalter, Lilian Camargo (2018)
The basin of the middle Paranapanema has a very anthropic landscape, with mosaic with large citrus areas, pastures and fragments of native vegetation. The medium and large mammals of this region were sampled for 14 months. The main objective of this study was to raise and understand the ecology of medium and large mammal species and how they use fragmented landscapes. In order to survey the community of medium and large mammals in the landscape, two methods were used: i) linear transect between native forest remnants and local monocultures (pasture, citriculture and soybean / corn; ii) complementary method interview with local residents. Twenty-five species were recorded through the linear transect method and 31 species were cited by the complementary method (these data were not used in the statistical analyzes). There was no significant difference between the sampled environments and the species richness (H = 2.70, p = 0.4402), nor the frequency of occurrence (H = 3.02, p = 0.3916). There was also no significant difference between species richness and frequency of occurrence in the seasons (H = 2.65, p = 0.3567, H = 4.4444, p = 0.3744, respectively). The second method worked positively with the collaboration and inclusion of local residents. The ethnoecological inventory presented greater species richness than the first one, which evidences the insertion of ethnoecological studies as a complementary methodology, since they contribute positively in studies of species survey. The data of this study corroborate other authors evidencing the urgency in the insertion of the agricultural landscape in studies, proposals and public policies that aim at the environmental conservation. It also demonstrates how the local population possesses a knowledge of the environments, species and interactions between them.